STATUS PEMANFAATAN LOBSTER MUTIARA (Panulirus ornatus) DI PERAIRAN PANTAI AYAH KABUPATEN KEBUMEN - Elvanri Anggi Widianti; Tri Wiji Nurani; Muhammad Fedi Alfiadi Sondita; Fis Purwangka; Prihatin Ika Wahyuningrum (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2021)
Sustainability is one of the essential issues in utilizing lobster in the coastal waters of Ayah, Kebumen Regency. Its management requires information on growth parameters and the utilization status of lobster. This study examines the growth parameters and utilization status of ornate spiny lobster (Panulirus ornatus) in the Ayah’s water. The study was conducted from November 2020 to January 2021. Lobster growth parameters were analyzed by distribution frequency of carapace length using the ELEFAN I method. Utilization status was estimated using spawning ratio based on carapace length data (LB-SPR). The results showed that the growth rate of males and females lobster was 0.37/year and 0.32/year, respectively. In addition, the asymptotic length was 145.70 mm in male lobsters and 143.33 mm in female lobsters. The exploitation rate is 0.41-0.48. The estimated spawning ratio is 29.59%, which means that it is still sustainable and below the optimum point.